Carbon Cloth Modified with Metal‐Organic Framework Derived CC@CoMoO4‐Co(OH)2 Nanosheets Array as a Flexible Energy‐Storage Material. Issue 13 (5th July 2019) - Zhao, Yunhe; Dong, Hongxing; He, Xinyi; Yu, Jing; Chen, Rongrong; Liu, Qi; Liu, Jingyuan; Zhang, Hongsen; Yu, Jia; Wang, Jun
Abstract: Due to the urgent demand for portable electronics, enormous research efforts are devoted for the development of flexible, wearable and lightweight supercapacitors. Herein, we report a cost‐effective chemical liquid process followed with a refluxing route to grow CC@CoMoO4 ‐Co(OH)2 nanosheets with Co‐based MOF as precursor. The resulting CC@CoMoO4 ‐Co(OH)2 ‐4 electrode delivers a significantly enhanced specific capacitance of 2028 F g − 1 at 1 A g −1 and capacitance of 1581.8 F g −1 at 20 A g −1 . Furthermore, the flexible all‐solid‐state asymmetric supercapacitor (CC@CoMoO4 ‐Co(OH)2 //AC) is assembled, displays a high energy density of 61 Wh kg −1 at power density of 800 W kg −1, with an excellent cycle stability. These exceptional electrochemical performances could be ascribed to the unique structure and multi‐metal ion combination contributes to the ideal synergistic effects, which also signify that the potential application of CC@CoMoO4 ‐Co(OH)2 nansheets in high‐performance supercapacitors. Abstract : MOF and cloth : We present a facile method for the synthesis of CC@CoMoO4 ‐Co(OH)2 materials using Co‐based MOF as the starting precursor, which show an excellent electrochemical performance for flexible all‐solid‐state supercapacitor.